The Traces of Spice Trade in Malay Text Records in the Riau Archipelago - Priyo Joko Purnomo (Regalia Institute, 2023)
The 18th until 19th century was a golden period/era of Riau Islands as a hub of spices trade in western Nusantara (Indonesia). In geographical aspect, Riau Islands border Malaka Strait to the west and the South China Sea to the north, so that this region was known as the gate of the world spices trade to Nusantara. The major commodities from Riau Islands is gambier which flourish in Tanjungpinang and catch the world’s attention. Foreigners who came and did trade in this region were welcomed by Malay society. A warm and dynamic interaction by Malay people with foreigners like Chinese, Arabs, and Indians generated certain cultural acculturation. That was proof that foreign culture was adapted to the prevailing culture of Malay society in the Riau Islands. This research aims to probe the trace of the spices trade in Riau Island which is written in Malay text in the form of hikayat, syair, and text about medicine and traditional medication. Several things discussed in this research are 1) the forms of cultural acculturation, 2) the uses of spices commodities, and (3) the roles of the spices trade center in the Riau Islands. The finding shows that the cultural interaction of Malay society in the Riau Islands is related to the history and the regional role as the gate and the hub of the world spices trade.